Adding granite polishing waste to reduce sand and cement contents and improve performance of mortar. (10th January 2021) - Chen, J.J.; Li, B.H.; Ng, P.L.; Kwan, A.K.H.
Abstract: Sand and cement are indispensable ingredients of concrete but their production is causing sustainability problems. Two strategies have been adopted to reduce their consumption, namely, sand replacement with solid waste and cement replacement with solid waste. However, sand replacement does not reduce cement content whereas cement replacement impairs performance. Herein, it is proposed that the two strategies may be combined to reduce the sand and cement contents without lowering performance. To evaluate the feasibility of such combined strategy, mortar mixes with granite polishing waste (GPW) added as sand and/or cement replacement were tested. It was found that adding GPW as sand replacement increased strength and durability whereas adding GPW as cement replacement increased flowability but decreased strength and durability. And, the contribution of the GPW arises mainly from the resulting improvement in particle packing. Lastly, among the mortar mixes tested, those with GPW added to replace 10% sand and 5% cement have better overall performance and lower sand and cement contents than the control mortar mix containing no GPW. This confirmed the desirable outcome of combined adoption of the sand and cement replacement strategies to reduce the sand and cement contents without impairing the performance. Highlights: Sand replacement strategy and cement replacement strategy are combined. Replacing sand by granite polishing waste (GPW) increases strength and durability. Replacing cement by GPW increases flowability, decreases strength and durability. GPW exerts its beneficial effects mainly through improving packing density. Replacing 10% sand and 5% cement by GPW enhances overall performance.